Protective Effect of Lutein/Zeaxanthin Isomers in Traumatic Brain Injury in Mice - Gunal, Mehmet Yalcin; Sakul, Ayse Arzu; Caglayan, Ahmet Burak; Erten, Fusun; Kursun, Oznur Ece Durmaz; Kilic, Ertugrul; Şahin, Kazım (Springer, 2021)
Previous studies revealed that oxidative stress and inflammation are the main contributors to secondary injury after traumatic brain injury (TBI). In an earlier study, we reported that lutein/zeaxanthin isomers (L/Zi) exert antioxidative and anti-inflammatory effects by activating the nuclear factor-kappa B (NF-kappa B) and nuclear factor-erythroid 2-related factor 2 (Nrf2) pathways. However, its precise role and underlying mechanisms were largely unknown after TBI. This study was conducted to investigate the potential mechanism of L/Zi isomers in a TBI model induced by a cold injury model in mice. To investigate the effects of L/Zi, male C57BL/6j mice-induced brain injury using the cold trauma model was allocated into two groups (n = 7): (i) TBI + vehicle group and (ii) TBI + L/Zi group (20 mg/kg BW). Brain samples were collected 24 h later for analyses. L/Zi given immediately after the injury decreased infarct volume and blood-brain barrier (BBB) permeability; L/Zi treatment also significantly reduced proinflammatory cytokines, including interleukin1 beta (IL-1 beta), interleukin 6 (IL-6), and NF-kappa B levels and increased growth-associated protein 43 (GAP-43), neural cell adhesion molecule (NCAM), brain-derived neurotrophic factor (BDNF), and Nrf2 levels compared with vehicle control. These data suggest that L/Zi improves mitochondrial function in TBI models, possibly decreasing inflammation and activating the Nrf2 pathway.
Keywords: Lutein/zeaxanthin isomers; Traumatic brain injury; NF-kappa B; Nrf2; BDNF